RBV Teori : Kinerja Religius Berbasis Kepribadian Islam dan Perilaku Inovatif Dalam Konseptual - Ali Jufri; Pebi Kurniawan; Mohammad Djadjuli; Imam Hadiwibowo (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2021)
This study tries to look at developments and emerging issues about resource-based displays. From the point of view of Penrose in 1959 about the need for companies to have competing resources, until Barney's compilation gave rise to a resource-based (RBV) view and valuable, rare, non-replicable, and irreplaceable (VRIN), and organizational (OIN) views in a place that can absorb and use them. Study reviews are used by using literature review studies by reviewing articles that are relevant to the theme. The RBV discussion starts with the 4-dimensional grouping of the RBV model, which is the focus of the renewal. The purpose of this study is to explore behavioral concepts in terms of Islamic personality that encourage innovative motivation so that individual targets can be increased not only because of the visible support for religious or belief in God.